Unraveling the cooperative mechanisms in ultralow copper-loaded WC@NGC for enhanced CO2 electroreduction to acetic acid - Bagchi, Debabrata; Riyaz, Mohd; Raj, Jithu; Roy, Soumyabrata; Singh, Ashutosh Kumar; Cherevotan, Arjun; Vinod, Chathakudath P.; Peter, Sebastian C. (Chemistry of Materials, 2024)
Electrochemical CO2 reduction reaction (eCO(2)RR) has been explored on tungsten carbide (WC) nanoparticles embedded on N-doped graphitic carbon (NGC), demonstrating excellent activity toward the formation of acetic acid at an extremely lower potential. The activity has been further enhanced by loading ultralow copper sites into the catalyst system, exhibiting 80.02% Faradaic efficiency (FE) toward acetic acid at an applied potential of -0.3 V (vs RHE). Potential-dependent in situ infrared (IR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, ex situ extended X-ray absorption fine structure (EXAFS) studies, and computational analysis confirm that synergy between uniformly dispersed Cu atoms and WC lattice plays a crucial role in the formation of acetic acid with high FE at a lower potential. It has been observed that the W atom of WC strongly chemisorbs CO2 with a significant change in the C-O bond length and the O-C-O bond angle, in contrast to weaker adsorption on Cu-based catalyst surfaces. The presence of a Cu site enhances the adsorption of CO2, thereby increasing the possibility of C-C coupling kinetically. Most importantly, hydrogen evolution predominates on the catalyst's surface at higher applied potentials (-0.5 to -1.1 V vs RHE), elucidating the mechanism underlying enhanced charge transfer between copper and WC, a phenomenon ascertained through in situ IR spectroscopy and ex situ XPS analysis

Ultra-small Pd nanoparticles on SBA-15: an efficient catalyst for one-pot reductive alkylation of nitrobenzene with size-dependent activity - Soni, Yogita; Philip, Milda C.; Vinod, Chathakudath P. (Topics in Catalysis, 2025)
One-pot reductive alkylation of nitrobenzene with alcohol is an important organic synthesis reaction to form 2 degrees amines. In the present work, we have demonstrated that Pd/SBA-15 can be an effective catalytic system for this reaction. We have designed ultra-small Pd nanoparticles supported on SBA-15 for the synthesis of secondary amine, N-ethylaniline, through one-pot reductive alkylation of nitrobenzene with ethanol under ambient conditions. Ethanol functions both as the alkylating agent and the solvent in this process. The reaction is driven by the simultaneous hydrogenation of nitrobenzene to aniline, dehydrogenation of ethanol to aldehyde, and condensation of aniline and acetaldehyde to form N-ethylaniline. The size of the Pd nanoparticles plays a decisive role in the product selectivity. The undercoordinated sites present on ultra-small Pd NPs can facilitate ethanol dehydrogenation to acetaldehyde, thereby enhancing the selectivity towards N-ethylaniline compared to larger Pd nanoparticles. We have also studied the effect of different mesoporous supports such as SBA-15, MCM-41, and KIT-6 on the N-ethylaniline selectivity and found that SBA-15 was most selective. We have demonstrated that by carefully designing the catalyst such as controlling the Pd NPs size to obtain the maximum quantity of undercoordinated sites and choosing suitable support, the aliphatic alcohols can also be used for reductive alkylation of nitrobenzene in one-pot with optimum yields of N-alkylaniline.
Keywords: KIT-6; MCM-41; Modified deposition precipitation; nitrobenzene; Pd nanoparticles; Reductive alkylation; SBA-15; secondary amines; Undercoordinated Pd sites